Thermodynamics of nanoparticles - Majerič, Peter; Rudolf, Rebeka; Anžel , Ivan (Anali PAZU, 2022)
This article deals with the basis for thermodynamic calculations of nanoparticles. Thermodynamics on the nanoscale are different than in bulk form, as there are more surface atoms with surface energy, which is different from bulk atom energy. This contribution of surface energy in nanoparticles changes the mechanisms of melting, grain growth, etc. compared to bulk materials. Using this starting point, one can use these calculations as a basis in nanoparticle synthesis processes. In our research we have synthesized nanoparticles with the process known as Ultrasonic Spray Pyrolysis. This is a versatile process, capable of producing nanoparticles from various materials such as gold, silver, titanium dioxide, nickel, nickel titanium, and so on.